HUBUNGAN KADAR GLUKOSA DARAH DENGAN KEJADIAN HIPERTENSI: STUDI CROSS-SECTIONAL DI RS SYARIF HIDAYATULLAH JAKARTA - Zulfa, Hilizza Awalina; Nofisah, Nur Lailatul; Nitalia, Mery; Hermawati, Luluk (Universitas Tadulako, 2026)
Hypertension is a condition characterized by an increase in systoic blood pressure >140 mmHg and/or diastolic blood pressure >90 mmHg. One of the important risk factors for hypertension is elevated blood glucose levels (hyperglycemia). This study aimed to determine the association between random blood glucose levels and the occurence of hypertension at Syarif Hidayatullah Hospital, Jakarta. This study employed an observational analytic design with a cross-sectional approach. A total of 90 respondents were included using consecutive sampling, with inclusion criteria of patients aged >18 years who had complete medical records of random blood glucose and blood pressure measurements. Bivariate analysis was performed using the Chi-Square test. The result showed that 42.2% of patients with hyperglycemia had hypertension, while 31.1% had hyperglycemia without hypertension. Among patients with normal blood glucose levels, 7.8% had hypertension and 18.9% had neither hypertension nor hyperglycemia. The Chi-Square analysis demonstrated a significant association between random blood glucose levels and hypertension (p = 0.017) with an odds ratio (OR) odf 2.588, indicating that patients with hyperglycemia had appoximately 2.6 times higher risk of developing hypertension compared to normoglycemic patients. In conclusion, there is a significant association between elevated random blood glucose levels and the occurance of hypertension, suggesting that hyperglycemia is an important risk factor for hypertension.